MANAJEMEN KONSERVASI ENERGI LISTRIK MELALUI PENDEKATAN FINANCIAL ASSESSMENT PADA PT XYZ - Ajen Mukarom; Abdul Kohar Irwanto; Armansyah H. Tambunan (Widyariset, 2014)
ThisresearchdiscussestheimplementationofelectricalenergyconservationmanagementatPT XYZ.The method used in this research utilizes measurement, survey, and interview. The data analysis includes descriptive analysis,EnergyConsumptionIntensity(IKE)measurement,identification ofenergysavingopportunities,and financialassessmentanalysisapproach.Theresultsofthisresearchshowthattheusagelevelandelectricalenergy costandIKEvalueon  PTXYZduring2012fluctuatedbuttheytendtodecline,theelectricityqualityofcosphi, electrical current unbalance, electrical frequency, voltage and current harmonic are still quite good.  However, the maximum value of electrical current unbalance exceeds the standard value, mainly in TR2/AC. Based on the observationandmeasurementontheOverallThermalTransferValue,ventilatingandairconditioning,andbuild- ing illumination areal system are suitable to the Indonesia National Standards (SNI). However, there are several ways to achieve the electrical energy conservation in ventilating and air conditioning, and lighting systems.MANAJEMEN KONSERVASI ENERGI LISTRIK MELALUI PENDEKATAN FINANCIALASSESSMENT PADAPTXYZ